Audit Quality And Accrual Quality: Do Big 4 Auditors Indeed Enhance Accrual Quality Of ‘Powerful’ Clients? - Park, Sorah (Journal of Applied Business Research, 2017)
External auditors are considered ‘watchdogs’ which closely monitor corporate financial reporting process and provide guidelines for investors and financial institutions. However, recent accounting scandals in Korea indicate that external auditors may cater their audit reports to their clients’ needs. Based on a sample of listed companies on the Korea Stock Exchange from 2001 to 2010, this study finds the evidence consistent with such conjecture. First, large business conglomerates in Korea (so called ‘chaebols’) audited by Big 4 have lower accrual quality than the others, indicating that Big 4 auditors may not serve as watchdogs to enhance accrual quality of ‘powerful’ clients. However, powerful clients who pay greater non-audit service fees to Big 4 auditors have higher accrual quality than the others. This result suggests that non-audit services provided by Big 4 may not necessarily harm the quality of accounting information, contrary to the traditional view in the literature.
Keywords: Accrual Quality; Audit Quality; External Auditor; Big 4; Chaebol